PENINGKATAN KEMAMPUAN BERPIDATO SISWA KELAS VIII MTS ALKHAIRAT PINOTU MENGGUNAKAN METODE MODELING - Idrus Idrus; Siti Hadija Alaydrus (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to determine the improvement of students' speaking ability through learning with the modeling method. This research is a classroom action research. The research subjects were all class VIII students of MTs Alkhairaat Pinotu for the 2020/2021 academic year, totaling 20 people, namely 12 boys and 8 girls. The method used in this research is the descriptive method. The design of this study refers to the Kemmis and McTaggart model which consists of four components, namely 1) planning, 2) action implementation, 3) observation, and 4) reflection. The data collected in this study is in the form of teacher and student activity data during the learning process obtained by using observation sheets and student learning outcomes data obtained by giving individual tests to students. In the research that has been carried out, it was found that for the Grade VIII students of MTs Alkhairaat Pinotu, the score of the pre-action speech students was 45% and then increased from 71.2 in the first cycle to 78.2% in the second cycle. The increase in the second cycle was due to the researchers placing more emphasis on the concept of motivating students to be bolder in speaking out from the reflection of the first cycle in giving speeches using the modeling method. While in cycle II, the researcher emphasized changing the model in learning. Thus, the application of modeling media can improve the achievement of speaking skills (speech) of class VIII MTs Alkhairaat Pinotu students so that the application of modeling media is carried out by teachers to improve student learning outcomes